Owners of Russian Personal Book Collections in the Turkestan Region - I. V. Lizunova; E. V. Pshenichnaya (Библиосфера)
The article is devoted to the owners of Russian personal libraries in Turkestan region at the end of the 19th – the beginning the 20th centuries, the persons who made a great contribution to creating the first public library of the European type on the territory of modern Uzbekistan. The purpose of the article is to consider the personality of the Russian personal libraries’ owners in the Turkestan region in the late 19th – early 20th centuries, as well as the history of the formation of their personal book collections, thematic content and the degree of their study. The article considers the peculiarities of the formation of Russian personal libraries, the composition and design of bibliophile collections, a variety of ownership characteristics. Russian personal book collections of the Turkestan region are of exceptional importance as a valuable source for the study of Russian book culture and socio-cultural development of the region.